FORMULASI DAN EVALUASI SEDIAAN LIP BALM DARI EKSTRAK KULIT BUAH DELIMA (Punica granatum L.) - Werawati, Ayu; Romlah, Siti Novy; Dewi, Bheta Sari; Sopian, Ahmad; Aulia, Gina; Manuruyah, Phuja Arinda (PHRASE (Pharmaceutical Science) Journal, 2025)
Lips are a part of the body that is easily damaged by environmental factors so that it requires special care, such as lip balm. Natural lip balm products are preferred because they are safe and effective for lip health. Pomegranate peel has high antioxidant and tannin content, but is still rarely used in cosmetics such as lip balm. The purpose of this study was to formulate and evaluate lip balm preparations from pomegranate peel extract (Punica granatum L.) with concentrations of 10%, 15% and 20%. The research method in this study is an experimental method with stages of lip balm preparation formulation and continued with examination of the physical quality of the preparation, namely homogeneity test, organoleptic test, pH test, adhesion test, and spreadability test.. The results showed that the observation of the color of the preparation was peach red, semi-solid in shape and had a distinctive odor of oleum cacao, pH 5.92-6.45 which had met the specification range. The conclusion of this study is that F1, F2 and F3 have met the requirements of organoleptic test, homogeneity, spreading power, adhesion, pH test.